Optimization of the fermentation technology and quality evaluation of highland barley and Potentilla anserine Jiaosu - WEN Huaying, WANG Fuyu, ZHANG Yuhong (Zhongguo niangzao)
Using 16 strains of Lactobacillus plantarum as the research objects, their acid and sugar tolerance were analyzed to select a fermentation strain with good tolerance, and highland barley and Potentilla anserine Jiaosu were prepared using the screened strain as starter culture, highland barley and P. anserine as main raw materials. With the superoxide dismutase (SOD) activity as the response value, the fermentation conditions were optimized by single factor tests and response surface tests, and the physicochemical index and antioxidant activity were analyzed. The results showed that L. plantarum LL6-1 was determined as the starter, the optimal fermentation parameters were as follows: P. anserine addition 9.6% supplemental level, fermentation time 4 d, and temperature 30 ℃. Under the optimized conditions, the SOD activity was 1 112.07 U/ml, and the contents of total acid, reducing sugar, amino acid, total phenol and flavonoid were 3.93%, 29.22 mg/ml, 1.06 μmol/ml, 3.03 mmol/L and 184.91 mg/L, respectively. In addition, the 1,1-diphenyl-2-picrylhydrazyl (DPPH), O2- and OH radicals scavenging capacity and Ferric ion reducing/antioxidant power (FRAP) were 1 710.18 μg Trolox/ml, 777.17 U/L, 1 701.31 U/ml and 6.39 μmol/ml, respectively, indicating the highland barley and P. anserine Jiaosu had antioxidant activity. The results of electronic tongue test showed that sour, bitter, sweet, astringent and umami were the taste indexes of the Jiaosu, and sour was the most prominent.